(untitled) (LACCEI, 2024)
This article presents a descriptive analysis of the work experience and level of training required by Peruvian public institutions for the recruitment of professionals related to information technology, computing or systems. The study proposes: identify the types of work experience and minimum training levels required for recruitment, determine the percentage of calls that require each type of experience, in general and according to the minimum time required, and determine the percentage of calls that require each level of training. training at a minimum. Three types of experience were identified: general, specific and in the public sector, as well as seven levels of training: student, graduate, bachelor’s degree, graduate, graduate and collegiate, teacher, doctor. The most required experience scheme considers general and specific experience at the same time and it represents 54% of calls. Professionals with a "bachelor" level were able to apply to 55.7% of calls, while those with a "graduate" level were able to apply to 98.76% of calls.